Lota España: Unpublished Manuscripts of Dolores González Pérez, a Writer Forgotten by Patriarchal Criticism and Historiography - Vela García, Dolores (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The purpose of this article is to present and to rescue the figure and work of the Andalusian writer Dolores González Pérez, also known as Lota España, whose unpublished texts and manuscripts have recently been found. In order to carry out an accurate exegesis, we will adopt the perspective of feminist criticism and hermeneutics, which will allow us to present the author and engaged into her personal and storyworld, through a corpus composed of more than 3000 texts of undoubted literary quality, including poetry, novels, short stories, essays, literary criticism and reviews, journalistic and opinion articles, etc. In addition, we will analyze some of the most significant contradictions around the author and her works, and how they influenced her literary production, and caused, in a decisive way, her writings to be forgotten and ignored by the patriarchal literary canon.